Pembelajaran Pendidikan Pancasila Kurikulum Merdeka pada Fase A: Sebuah Analisis - Karima, Muhammad Kaulan; Romadhon Hafild, M. Nazali; Putri, Tiya Permana; Damayanti, Frianka Ivana; Andini, Dea; Wulansari, Shella Dyah (STKIP PGRI Bandar Lampung, 2025)
Pancasila education is an educational program that aims to instill the basic values ​​of Pancasila in society, especially students from an early age. This education focuses on the five principles in the Pancasila of Godhead, Humanity, Unity, Democracy and Justice - which reflect the basic values ​​of the Indonesian nation. Through Pancasila education, students are taught to understand and apply moral, social and nationalist values ​​that support national unity, respect diversity and encourage participation in national life. In the Merdeka curriculum, Civics learning outcomes for phase A students include the introduction of Pancasila symbols and principles, application of Pancasila values ​​in everyday life, and respect for diversity. Analysis at SDN 1 Langkapura shows that learning Pancasila education is still limited to memorizing the principles of Pancasila, without a deep understanding of its values, as well as students' lack of mastery of the concept of rights and obligations. This emphasizes the importance of using contextual and interactive approaches, such as role playing and practical activities, to facilitate learning that is appropriate to students' developmental stages of thinking. Apart from that, increasing teacher competence and integrating Pancasila values ​​in daily learning is the key to achieving optimal learning goals